Hemocompatibility Testing of Blood-Contacting Implants in a Flow Loop Model Mimicking Human Blood Flow - Link, Antonia; Cattaneo, Giorgio; Brynda, Eduard; Riedel, Tomas; Kucerova, Johanka; Schlensak, Christian; Wendel, Hans Peter; Krajewski, Stefanie; Michel, Tatjana (Journal of visualized experiments, 2020)
The growing use of medical devices (e.g., vascular grafts, stents, and cardiac catheters) for temporary or permanent purposes that remain in the body's circulatory system demands a reliable and multiparametric approach that evaluates the possible hematologic complications caused by these devices (i.e., activation and destruction of blood components). Comprehensive in vitro hemocompatibility testing of blood-contacting implants is the first step towards successful in vivo implementation. Therefore, extensive analysis according to the International Organization for Standardization 10993-4 (ISO 10993-4) is mandatory prior to clinical application. The presented flow loop describes a sensitive model to analyze the hemostatic performance of stents (in this case, neurovascular) and reveal adverse effects. The use of fresh human whole blood and gentle blood sampling are essential to avoid the preactivation of blood. The blood is perfused through a heparinized tubing containing the test specimen by using a peristaltic pump at a rate of 150 mL/min at 37 °C for 60 min. Before and after perfusion, hematologic markers (i.e., blood cell count, hemoglobin, hematocrit, and plasmatic markers) indicating the activation of leukocytes (polymorphonuclear [PMN]-elastase), platelets (β-thromboglobulin [β-TG]), the coagulation system (thombin-antithrombin III [TAT]), and the complement cascade (SC5b-9) are analyzed. In conclusion, we present an essential and reliable model for extensive hemocompatibility testing of stents and other blood-contacting devices prior to clinical application.
Keywords: pankreatická elastasa; beta-Thromboglobulin; Blood Specimen Collection; Blood Circulation; komplement; cévní protézy; krevní obraz; Heparin; krevní plazma; odběr vzorku krve; imunitní systém; Models, Biological; beta-thromboglobulin; Blood Cell Count; Humans; krevní oběh; biologické markery; stenty; biologické modely; Immune System; Stents; Blood Vessel Prosthesis; heparin; Pancreatic Elastase; Biomarkers; Complement System Proteins; testování materiálů; Plasma; Materials Testing; lidé